KOMPETENSI APARATUR LAYANAN PERIZINAN ONLINE SINGLE SUBMISSION DI KOTA BOGOR - Agung Nurrahman; Naomi Tirahani; Eko Budi Santoso; Rusmini Rusmini (Jurnal Ilmu Pemerintahan Widya Praja, 2021)
One of the licensing services provided by the Office of Investment and One Stop Integrated Services (DPMPTSP) of Bogor City is through the Online Single Submission (OSS) service. However, since it was launched in 2018 until now, the government has never held education and training related to OSS in order to increase the competence of the apparatus. The purpose of this study is to describe the competence of the apparatus in providing online single submission licensing services at the Bogor City Investment and One Stop Integrated Service Office. This research is a type of qualitative descriptive research that uses interviews, observations and documentation. Interviews were conducted using a planned-unstructured technique to 12 research informants. The results show that by using the theoretical basis of competence according to Spencer and Spencer (1993 in Sutrisno, 2019) which includes 5 dimensions, namely motives, traits, self-concept, knowledge, and skills, in aggregate the competence of the Bogor City DPMPTSP apparatus can be stated to be quite good. However, several competency indicators on the skills dimension show some weaknesses, especially on indicators of administrative and managerial skills related to SOPs for handling complaints. Likewise in the knowledge dimension, relatively still needs to be improved. This happens because the apparatus has never participated in special training regarding the implementation of OSS services. Keywords: Public Servant, Competence, Public Service, Online Single Submission